2022
DOI: 10.1007/s10072-022-06235-0
|View full text |Cite
|
Sign up to set email alerts
|

Tics: neurological disorders determined by a deficit in sensorimotor gating processes

Abstract: Tic related disorders affect 4–20% of the population, mostly idiopathic, can be grouped in a wide spectrum of severity, where the most severe end is Tourette Syndrome (TS). Tics are arrhythmic hyperkinesias to whom execution the subject is forced by a “premonitory urge” that can be classified as sensory tic, just-right experience or urge without obsession. If an intact volitional inhibition allows patients to temporarily suppress tics, a lack or deficit in automatic inhibition is involved in the genesis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Иммунные клетки способны продуцировать нейропептиды и нейротрансмиттеры, такие как серотонин, ацетилхолин и эндорфины. Изменения в путях синтеза дофамина и серотонина могут быть вовлечены в патофизиологию COVID-19 и обуславливать развитие тикозных гиперкинезов [55][56][57][58][59][60][61][62][63].…”
Section: тикиunclassified
“…Иммунные клетки способны продуцировать нейропептиды и нейротрансмиттеры, такие как серотонин, ацетилхолин и эндорфины. Изменения в путях синтеза дофамина и серотонина могут быть вовлечены в патофизиологию COVID-19 и обуславливать развитие тикозных гиперкинезов [55][56][57][58][59][60][61][62][63].…”
Section: тикиunclassified
“…For example, in the case of obsessive-compulsive disorder (OCD), the deficit in patients varies depending on methodological differences among studies [ 68 ], as differences with controls or normal PPI ratios are found depending on the psychopharmacological status of the patients [ 71 , 72 ]. However, it appears that the deficit in OCD is mediated by the prior presence of tics among patients [ 71 ], which makes sense considering the clear sensorimotor gating deficit in Gilles de la Tourette syndrome [ 34 , 73 , 74 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, deficits in inhibitory circuits in children and adolescents with TS might be compensated by reducing the gain in corticospinal excitability. Consequently, this would lead to decreased sensitivity to changes in input from other brain areas or external stimuli ( Schilke et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%